Reformasi Pelaku Tindak Pidana Yang Mengidap Penyakit Jiwa: Perbandingan Hukum Pidana Indonesia dan Belanda - Indratmoko, Daryll Alessandro; Hakim, Arief Rachman (Legal Spirit, 2025)
Mental illness is one of the things that is quite complicated, especially in its regulation in the field of law, there must be a good and effective special arrangement or treatment for offenders with mental illness in the process of punishment to punishment and action, based on that, a comparative study can be carried out to find out the advantages and disadvantages which can then be taken into consideration to be applied in Indonesia, in this study using the Netherlands which has a long historical background with Indonesia.This research uses normative juridical and then analyzed descriptively and uses a qualitative approach. The results showed that the Netherlands has advantages in the judicial process and the provision of punishment and action, namely first in the judicial process itself in the Netherlands there are external institutions that will help the judicial process to be more efficient and also this external institution itself can guarantee the competence and credibility of the judicial process against offenders with mental illness, then in the provision of punishment and action the Netherlands has more detailed regulations, namely there are additional laws such as forensic laws, especially psychiatric forensics which are certainly very much needed and also laws around providing treatment if the offender is forced to serve a sentence, of course this is very much needed in dealing with offenders with mental illness because the nature of mental illness itself is quite complex.